Pembelajaran Bahasa Indonesia berbasis Eko-Kultural untuk Penguatan Edu-Wisata di Kawasan Taman Nasional Bromo Tengger Semeru - Ahmad Syukron; Arief Rijadi (Universitas Muhammadiyah Jember, 2024)
Indonesian language learning is the right vehicle for presenting content-based learning because it is text-based learning. Recently, eco-culture has become a trend again as evidenced by various things being built and branded as policies, technology, products, goods and services based on eco-culture. In practice, Indonesian language learning in schools has the potential to be designed as content-based learning with an eco-cultural approach. Through the integration of Indonesian language learning with content based on an eco-cultural approach, it is hoped that Indonesian language learning in schools will provide support for the development of eco-cultural-based edu-tourism in Indonesia. Eco-Cultural Based Indonesian Language Learning to Strengthen Edu-Tourism in the Bromo Tengger Semeru National Park Area